ON THE ARRIVAL TIME, WAITING TIME TO UPLOAD , UN LOADING TIME AND WAITING TIME FOR DEPARTURE FOR PURSE SEINERS AT MANGALORE LANDING CENTRE - UDUPA, K S; RAO, B. V NARAHARI; REDDY, T. N VENKATA (Fishery Technology, 2017)
Fifty four purse-seine boats at Mangalore landing centre were observed during different stages of unloading fish catch. It was found that a boat takes 75% of the berthing time to unload an average quantity of 2.4 tonnes of fish. Further, unloading period and r.atch were found to be directly related where it was estimated that 5 to 7 minutes are E'pent in unloading about half a tonne of fish to a nearb)' tempo by employing 9 + 2 labourers.